Moringa oleifera as the potential herb medicine for neurodegenerative diseases: a narrative review - Dewi, Yulia Ratna; Barinda, Agian Jeffilano; Arozal, Wawaimuli (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2024)
Neurodegenerative diseases, such as Alzheimer's and Parkinson's, significantly burden the global older adult population. These diseases are characterized by the degeneration of nerve cells and subsequent damage, leading to the gradual loss of neurological function and subsequently affecting the quality of life of older adult people. This study explores the potential role of Moringa oleifera (MO) on neurological diseases. MO, a plant rich in bioactive compounds such as flavonoids, polyphenols, saponins, and tannins, has been proven to possess potent antioxidant effects. Oxidative stress is a primary contributor to the pathogenesis of neurodegenerative diseases, and MO can protect nerve cell damage by enhancing antioxidant activity. In the context of Parkinson's disease, MO has demonstrated the ability to reduce cataleptic symptoms and protect dopaminergic neurons, which are crucial in preventing a decline in dopamine production in the brain. In Alzheimer's disease, MO can improve memory function, reduce oxidative stress, and inhibit the activity of Acetylcholinesterase (AChE) enzymes involved in neurotransmitter dysfunction. While further research is needed to gain a deeper understanding of MO's mechanisms and more specific therapeutic potential, the existing evidence suggests that its constituents and effects hold significant promise as a natural solution for combating the effects of neurodegenerative diseases. As the number of individuals affected by these diseases continues to rise worldwide, further investigation into MO as a neuroprotective agent could pave the way for developing more effective therapies for these conditions.